(3ebOeI aj Yde GdJMdjd GdeQcH (B/s - (3GdWhjd, eLOjs ((3GdbGgQI(B: s (3OGQ GdfTQ ddLGeYGJ(B, s, 2005)
(3OhGd GdeJZjQ GdeQcH(B- (3GdfgGjGJ(B- (3GdESJeQGQ(B- (3GdETJbGb(B- (3JcGed GdOhGd GdeQcH(B- (3fXQjI GdHGbj(B- (3JWHjbGJ aj JcGed GdeMOhO(B- (3GdCYOGO GdeQcHIs
Keywords: (3GdESJeQGQs; (3GdETJbGbs; (3GdOhGds; (3GdOhGd GdeQcHIs; (3GdfgGjGJs